Associations between weight stigma and mental well-being among people in romantic relationships: an actor-partner interdependence model investigation - Brochu, Paula M.; Georgia, Emily J.; Jubran, Madeline; Robbins, Molly; West, Katherine; Crocker, Jillian; Schmidt, Alexandria M.; Rinaldi, Katerina; Joseph, Em; Roddy, McKenzie K. (Frontiers in Psychiatry, 2025)
BackgroundRomantic relationships are primary sources of mental well-being, including life satisfaction. Stigma not only has adverse effects on individual mental well-being but also negatively affects relationship functioning. The purpose of this dyadic, cross-sectional study was to examine the associations between internalized, anticipated, and experienced weight stigma and mental well-being among people in romantic relationships and their partners.MethodProlific, an online crowdsourcing platform, was used to recruit 287 couples in long-term relationships who resided in the United States. Participants completed measures of internalized weight stigma, anticipated weight stigma, experienced weight stigma, and mental well-being. Actor-partner interdependence models estimated the associations between participants’ weight stigma and their own mental well-being (actor effect) and the mental well-being of their romantic partners (partner effect).ResultsAs expected, significant negative associations were observed between participants’ internalized, anticipated, and experienced weight stigma and their own mental well-being; these actor effects had small to medium effect sizes. Significant negative associations were also observed between participants’ internalized and anticipated weight stigma and their partners’ mental well-being; these partner effects had small effect sizes. Unexpectedly, a significant partner effect was not observed for experienced weight stigma.ConclusionsWeight stigma is negatively associated with individual mental well-being as well as the mental well-being of romantic partners. Future research is needed to replicate and expand these findings and examine internalized and anticipated weight stigma as potential mechanisms through which experienced weight stigma may affect mental well-being among people in romantic relationships and their partners.